Epigenetic regulation of defense genes by histone deacetylase1 in human cell line-derived macrophages promotes intracellular survival of Leishmania donovani. - Gargi Roy; Harsimran Kaur Brar; Rohini Muthuswami; Rentala Madhubala (Public Library of Science (PLoS), 2020)
Leishmania donovani, an intracellular protozoan parasite upon infection, encounters a range of antimicrobial factors within the host cells. Consequently, the parasite has evolved mechanisms to evade this hostile defense system through inhibition of macrophage activation that, in turn, enables parasite replication and survival. There is growing evidence that epigenetic down-regulation of the host genome by intracellular pathogens leads to acute infection. Epigenetic modification is mediated by chromatin remodeling, histone modifications, or DNA methylation. Histone deacetylases (HDACs) removes acetyl groups from lysine residues on histones, thereby leading to chromatin remodeling and gene silencing. Here, using L. donovani infected macrophages differentiated from THP-1 human monocytic cells, we report a link between host chromatin modifications, transcription of defense genes and intracellular infection with L. donovani. Infection with L. donovani led to the silencing of host defense gene expression. Histone deacetylase 1 (HDAC1) transcript levels, protein expression, and enzyme activity showed a significant increase upon infection. HDAC1 occupancy at the promoters of the defense genes significantly increased upon infection, which in turn resulted in decreased histone H3 acetylation in infected cells, resulting in the down-regulation of mRNA expression of host defense genes. Small molecule mediated inhibition and siRNA mediated down-regulation of HDAC1 increased the expression levels of host defense genes. Interestingly, in this study, we demonstrate that the silencing of HDAC1 by both siRNA and pharmacological inhibitors resulted in decreased intracellular parasite survival. The present data not only demonstrate that up-regulation of HDAC1 and epigenetic silencing of host cell defense genes is essential for L. donovani infection but also provides novel therapeutic strategies against leishmaniasis.